Effects of crude methanolic leaf extract of Clinacanthus nutans (Burm.f.) lindau on high-fat diet-induced obese mice - Abdulwahid, Samiaa Jamil (2019)
Obesity is a major health concern that has reached epidemic proportions globally. Malaysia has the highest obesity rate at 14% in the Southeast Asia region. The cost and side effects of synthetic anti-obesity drugs necessitate the finding of suitable herbal alternatives. The current study investigated the antiobesity effects of Clinacanthus nutanus crude leaf extract in 80 % methanol (MECN). The sub-acute oral toxicity of MECN was evaluated in 6-week- old ICR mice (21 males, 21 females). The mice were randomly divided into six treatment groups of seven animals each, comprising of untreated control, mice treated with 1000 and 2000 mg/kg MECN, for males and females. Animals were gavaged with the treatment agents once daily for 28 days. Despite the incidental lesions noted for the livers and kidneys, there no difference (P>0.05) between the histolopathological changes seen among mice treated with MECN, and that of the untreated controls in both sexes. No significant changes were also noted for the physical, hematological and serum biochemical parameters between the control and treatment groups for both sexes. However, the serum sodium level in mice treated with 2000 mg/kg MECN was lower than the controls (P<0.05). In the ensuing experiment, MECN was used at 2000 mg/kg as a potential anti-obesity agent in obese mice. Fifty (4-weeks-old) male mice were randomly assigned into 2 groups: (1) a normal diet group (NC, n=10); and (2) treatment group (fed a high-fat diet for 16 weeks, n=40). At 20 weeks of age, the mice fed high-fat diet were randomly assigned into 4 sub-groups comprising of, high-fat diet only (HFDC); MECN at 500 mg/kg (HFD+CN500); 1000 mg/kg (HFD+CN1000) and 1500 mg/kg (HFD+CN1500). All mice were then subjected to 21 days of treatment. The current study showed that MECN treatment at 1000 and 1500 mg/kg reduced body weight, relative visceral fat, serum lipid profile, malondialdehyde (MDA) levels in muscle, cholesterol and saturated fatty acid composition (P<0.05). Visceral fat among MECNtreated mice showed significant decrease (P<0.05) in hypertrophic adipocyte cell size compared to the HFDC group after treatment. The PPARγ and SCD1 genes expression were down-regulated, especially in mice fed with 1000 and 1500 mg/kg of MECN compared to the HFDC group. Mice treated with MECN at 1500 mg/kg showed a decreased PPARα expression, and an increased expression of HSL mRNA. In terms of adipocytokines, mice treated with MECN at 1000 and 1500 mg/kg showed a significantly (P<0.05) elevated level of adiponectin, and reduced levels (P<0.05) of leptin, interleukin-6 (IL-6), and tumor necrosis factor-α (TNFα) compared to the HFDC. In summary, the results suggested that MECN could ameliorate diet-induced obesity via the regulation of gene expressions and adipocytokines involved in lipid metabolism. However, future clinical trials are necessary to ascertain its clinical efficacy.